Data set for analysis of Customer preference and demand for reduced cooking time bean varieties on the Ugandan markets - Katungi, Enid Mbabazi; Asiimwe, Robert; Mukankusi, Clare; Rubyogo, Jean Claude (2025)
The data were used to analyse Ugandan consumer preferences for bean varieties with reduced cooking time, comparing rural producers and urban consumers. Using a discrete choice experiment, it assessed the value placed on attributes like cooking time, grain swelling, taste, color, climate resilience, yield, and price. These attributes were identified through stakeholder consultations and literature for their relevance to nutrition, food security, and climate goals. A latent class model was used to estimate preferences, as reduced-cooking-time beans are not yet commercially available. The objective was to inform breeding priorities by identifying the bean attributes consumers value most. A key focus was determining if preferences differed significantly between rural bean-producing households and urban non-producing consumers Methodology:Data were collected from consumers across Uganda's major bean-growing and consuming regions via household and community surveys. The household survey, administered digitally using ODK/SurveyCTO, was conducted to either the household head or their spouse. It covered nine modules, including: 1) demographics and socio-economics, 2) bean consumption and preparation, 3) a choice experiment and willingness-to-pay questions and 4) agricultural production, assets, and food consumption. Respondents were guided through the choice experiment in English or local dialects.